ANALISIS KARAKTER PROTAGONIS DALAM FILM “PERFUME: THE STORY OF A MURDERER” - Hakim, Agus; M. Firdaus Benyamin; Budiman, Budiman (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2024)
This article contains the results of the analysis of the protagonist's character in the film